Multifaceted effects of soluble human CD6 in experimental cancer models. Issue 1 (26th March 2020) - Simões, Inês T; Aranda, Fernando; Casadó-Llombart, Sergi; Velasco-de Andrés, María; Català, Cristina; Álvarez, Pilar; Consuegra-Fernández, Marta; Orta-Mascaró, Marc; Merino, Ramón; Merino, Jesús; Alberola-Ila, José; González-Aseguinolaza, Gloria; et al.
Abstract : Background: CD6 is a lymphocyte surface co-receptor physically associated with the T-cell receptor (TCR)/CD3 complex at the center of the immunological synapse. There, CD6 assists in cell-to-cell contact stabilization and modulation of activation/differentiation events through interaction with CD166/ALCAM (activated leukocyte cell adhesion molecule), its main reported ligand. While accumulating evidence is attracting new interest on targeting CD6 for therapeutic purposes in autoimmune disorders, little is known on its potential in cancer. In an attempt to elucidate the in vivo relevance of blocking CD6-mediated interactions in health and disease, we explored the consequences of expressing high circulating levels of a soluble form CD6 (sCD6) as a decoy receptor. Methods: High sCD6 serum levels were achieved by using transgenic C57BL/6 mice expressing human sCD6 under the control of lymphoid-specific transcriptional elements (shCD6LckEμTg) or wild type either transduced with hepatotropic adeno-associated virus coding for mouse sCD6 or undergoing repeated infusions of recombinant human sCD6 protein. Characterization of sCD6-induced changes was performed by ex vivo flow cytometry and functional analyses of mouse lymphoid organ cells. The in vivo relevance of those changes was explored by challenging mice with subcutaneous or metastatic tumors induced by syngeneic cancer cells of different lineage origins. Results: Through a combination of in vitro and in vivo studies, we show that circulating sCD6 expression induces defective regulatory T cell (Treg) generation and function, decreased CD166/ALCAM-mediated tumor cell proliferation/migration and impaired galectin-induced T-cell apoptosis, supporting the fact that sCD6 modulates antitumor lymphocyte effector function and tumorigenesis. Accordingly, sCD6 expression in vivo resulted in delayed subcutaneous tumor growth and/or reduced metastasis on challenge of mice with syngeneic cancer cells. Conclusions: Evidence is provided for the disruption of CD6 receptor–ligand interactions as a feasible immunomodulatory approach in cancer.